A comparative clinical study of bioceramic and calcium hydroxide based root canal sealer in the treatment of non-vital permanent tooth with periapical lesion (Update Dental College Journal, 2021)
Introduction: The use of Bioceramic sealer in the obduration of the root canal system has been expected by many of the previous studies. However, the clinical outcome has not yet been established.Objective: To compare the effectiveness of bioceramic and calcium hydroxide based root canal sealer in treatment of non-vital permanent teeth with periapical lesion (Periapical periodontitis).Materials and Methods: A total 100 mature permanent anterior teeth were selected after clinical and radiological examination which had non-vital pulp with periapical lesion. Clinically pulp vitality test, palpation and percussion test was performed maintaining standard procedure. Following cavity preparation and biomechanical preparation, each canal was obturated either with bioceramic (Endosequence BC) or calcium hydroxide based sealer  (Sealapex, Kerr). All participants were evaluated immediately after obturation, at  3 and 6 months for the assessment of change in size of periapical lesion, condition of periodontal ligament space, lamina dura and incidence of post-operative pain, swelling. Statistical analysis was performed using Chi- square(X2) test and t-test. A value of p